Land Potency for Dairy Cattle at East Slope of Merapi-Merbabu Volcano, Boyolali, Central Java - Yuli Priyana (Universitas Muhammadiyah Surakarta, 2004)
Research about farm potency for the livestock of diary attle is held in east volcano side of Merapi – Merbabu Boyolali regeny. This famous area represent dairy attle livestock sentra in Boyolali regeny. From the holdness above emerging question why dairy cattle livestock expand at area. This research aim to study which area which are potential for the livestock of dairy cattle and also physical fator what most having an effect to density of dairy cattle livestock, what is availability of water, mean temperature, height of place, accesibility. The methods use in the research is analysis of secondary data provided with survey. To know the condition of physical what most having an effect on density (availability of water, mean air temperature, height of place, accesibility) to use test of multiple regression. To know dairy cattle livestock farm potency joined with others compile map of availability of water, map of temperature, map of height of place, and map of accesibility. The result of researh indicate that most having an effect to density to dairy cattle livestock press out accesibility. Potency farm area of the livestock of dairy cattle about of height 700 m of sea water level, around region sub district of Cepogo, Selo, and Musuk. Musuk, this area represent area having cold limate enough. Research area having density of highest dairy cattle livestock is district of Musuk.